Cross‐cultural Measurement Invariance of the Employment Opportunity Index (EOI) in Mexican and Brazilian Professionals. (June 2014) - Morse, Brendan J.; Weinhardt, Justin M.; Griffeth, Rodger W.; de, Manoela Ziebell
<x xml:space="preserve">Abstract</x> Perceived employment alternatives have been shown to add incremental variance in understanding voluntary turnover as well as factors related to recruiting and staffing. The Employment Opportunity Index (EOI) is a multidimensional assessment of perceived employment alternatives that has exhibited predictive validity across multiple job types and populations. This study assessed the measurement invariance of the EOI in American, Mexican, and Brazilian professionals. We found support for configural and metric invariance in all five dimensions of the EOI with these populations, and support for scalar invariance three of the five EOI dimensions. The construct validity of the EOI appears to be relatively robust in Latin American populations, although cultural and macroeconomic factors may impose some response bias in these groups.